Together Yet Apart. The Institutional Rift Among Lebanese-Muslims in a South American Triple Frontier and Its Origins - Elmaleh, Omri (Anuario de Historia de América Latina, 2019)
On October 1988, the first mosque in the Triple Frontier between Argentina-Brazil-Paraguay was inaugurated. The name given to the mosque rekindled old and modern disputes amongst local Lebanese-Muslims in the region and led to the creation of parallel religious and cultural institutions. Based on oral history and local press, the article illustrates how the inauguration of the mosque and its aftermath reflected an Islamic dissension and Lebanese inter-religious and ethnic tensions that were "exported" to the Triple Frontier during the 1980s. The article also argues that the sectarian split among the leadership of the organized community, was not shared by the rank and file and did not reflect their daily practices.
Keywords: Organized Community, Lebanese Civil War, Sunni-Shiite Schism, Transnationalism, Diaspora.